3D scanning and geometry processing techniques for customised hand orthotics: an experimental assessment. Issue 2 (3rd April 2018) - Volonghi, Paola; Baronio, Gabriele; Signoroni, Alberto
ABSTRACT: In the field of rehabilitation, the 3D scanning of body parts can be considered a crucial starting point for subsequent 3D model design of customised devices, especially when additive manufacturing techniques are involved in their production. This study experimentally evaluates and identifies appropriate procedures to acquire and process 3D anatomic images of the hand, including fingers, for the design of customised orthoses. Hand scanning is a complex activity and requires solutions capable of solving problematic aspects, such as the difficulty in maintaining the hand in a steady position and the presence of motion artefacts due to involuntary movements. We addressed such issues by considering the use of two different kinds of optical scanning device. The acquisition process has been initially defined based on healthy subjects and then extended to patients affected by pathologies that compromise upper limb functionality. Quality anatomical models were produced thanks to the application of advanced geometry processing technologies for the automated alignment of multiple scans and the removal of artefacts due to involuntary movements. As a result, with distinctive pros and cons, both the proposed combinations of scanning procedures and dedicated geometry processing evidenced their suitability in producing complete and accurate enough 3D models to be exploited for the subsequent design and production of customised hand orthoses in a typical reverse engineering pipeline.